Health Literacy and Qualitative Research: Bridging Socio-Cultural Factors, Technology, and Policy - Walujo , Djembor Sugeng (Yayasan Sinergi Kawula Muda, 2025)
Health literacy, defined as the ability to access, comprehend, evaluate, and apply health information, has emerged as a vital determinant of health outcomes. This narrative review aimed to explore how qualitative methodologies contribute to understanding health literacy. Specifically, it sought (1) to examine how qualitative methods capture the lived experiences shaping health literacy, (2) to analyze the role of socio-cultural and technological factors, and (3) to identify methodological gaps and innovations. A total of 58 peer-reviewed studies were included in this review. Inclusion criteria focused on English-language, peer-reviewed studies published within the last decade, with an emphasis on vulnerable populations. Findings reveal that in-depth interviews, focus group discussions, thematic analysis, and photovoice are widely used to capture the lived experiences and social contexts that shape health literacy. Results highlight the strong influence of socio-cultural norms, traditional practices, and social support networks, while digital innovations such as mobile health tools and online platforms offer promising but unevenly distributed benefits. Challenges persist, including methodological limitations, underrepresentation of vulnerable populations, and systemic barriers such as social inequality, weak infrastructure, and limited education. The discussion emphasizes the importance of participatory, community-based interventions, culturally sensitive communication, and equitable integration of digital technologies. Future research should prioritize longitudinal and cross-contextual studies to address gaps and evaluate long-term outcomes. Overall, qualitative approaches provide indispensable insights into health literacy and can guide the development of policies and interventions that are contextually relevant and globally applicable.